Design of Control System of Hydrogen and Oxygen Flow Rate for Proton Exchange Membrane Fuel Cell Using Fuzzy Logic Controller - Thomya A. (2014)
This research studies to develop design and construct a prototype of the operation control system of Proton exchange membrane fuel cell. The experimental results show that the performance of fuel cell depends on gas flow rate, temperature, humid and operating pressure. Therefore, the control system performance in the aspect of these parameters is evaluated. The control system performance was determined by comparing between control flows generated from simulations control with flow rate of a self-created, used fuzzy logic control. It was observed that the external load changes the current output proportionally to comply with the requirements; Power was control by voltage was 0.6. Enhancement during a constant load and its time strongly depends on the operational current level. This genetic fuzzy controller demonstrates improved response than manual control. This predictive control is accomplished by the use of fuzzy logic. Finally shows the prototype operation control system which easy controlled to optimization of the fuel cell performance and it can portable control system.